The definitive handbook of business continuity management / edited by Andrew Hiles. - Hiles, Andrew (Wiley, 2011)
With a pedigree going back over ten years, The Definitive Handbook of Business Continuity Management can rightly claim to be a classic guide to business risk management and contingency planning, with a style that makes it accessible to all business managers. Some of the original underlying principles remain the same - but much has changed. This is reflected in this radically updated third edition, with exciting and helpful new content from new and innovative contributors and new case studies bringing the book right up to the minute. This book combines over 500 years of experience from leading.